NMCP‐2 polysaccharide purified from Morchella conica effectively prevents doxorubicin‐induced cardiotoxicity by decreasing cardiomyocyte apoptosis and myocardial oxidative stress. Issue 11 (15th September 2021) - Xu, Na; Lu, Yi; Yao, Xinmiao; Zhao, Rui; Li, Zhebin; Li, Jialei; Zhang, Yinglei; Li, Bo; Zhou, Ye; Shen, Huifang; Wang, Liqun; Chen, Kaixin; et al.
Abstract: Doxorubicin (DOX) is an anthracycline antibiotic used in the clinical treatment of cancer, but its use is limited due to its cardiotoxic effects. Therefore, it is necessary to explore natural compounds that are effective in protecting against the cardiotoxicity caused by DOX. Neutral Morchella conica polysaccharides‐2 (NMCP‐2) is a natural polysaccharide with antioxidant activity that was isolated and purified from Morchella conica in our laboratory's previous study. This study aimed to investigate the possible protective effect of NMCP‐2 on DOX‐induced cardiotoxicity and the potential underlying mechanisms. The model of DOX‐induced H9C2 cells and the model of DOX‐induced mice were used in this study. In in vitro studies of H9C2 myocardial cells, NMCP‐2 effectively increased the activity of H9C2 cells, reducing the levels of lactate dehydrogenase (LDH). In the mouse model of DOX‐induced chronic cardiotoxicity, NMCP‐2 significantly reduced the cardiac index, reduced the release of serum cardiac enzymes, and improved the pathology of murine myocardial tissues, thereby alleviating DOX‐induced cardiotoxicity. Further mechanism studies showed that pretreatment with NMCP‐2 counteracted the oxidative stress induced by DOX, as indicated by increasing superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) activities, and malondialdehyde (MDA) production decreased. In addition, we observed NMCP‐2 inhibited the activation of the mitochondrial apoptosis pathway and regulated the disordered expression of Bcl‐2 and Bax in the myocardial tissues of DOX‐treated mice. These findings indicated that NMCP‐2, a natural bioactive compound, could potentially be used as a food supplement to reduce the cardiotoxicity caused by DOX. Abstract : NMCP‐2 polysaccharide is a natural polysaccharide with antioxidant activity that was isolated and purified from Morchella conica . This study aimed to investigate the possible protective effect of NMCP‐2 on DOX‐induced cardiotoxicity and the potential underlying mechanisms. The results showed that NMCP‐2 exerts a definite effect on DOX‐induced myocardial injury. This effect may be associated with the inhibition of oxidative stress and subsequent mitochondria‐dependent apoptotic pathways. Therefore, NMCP‐2 as a natural bioactive compound can be a potential food supplement for reducing the cardiotoxicity caused by DOX.